Examination of the attitudes of preschool teacher candidates and teacher candidates in other branches towards scientific research in terms of some variables - Yaşar Ekici, Fatma; Ekici, Fatma Yaşar (Eurasian Society of Educational Research, 2017)
The main objective of this study is to examine the attitudes of preschool teacher candidates and teacher candidates in other branches towards scientific research in terms of some variables. Survey method was used. The study group consists of 547 teacher candidates studying in education faculty of a private university in the spring term of 2015-2016 in Istanbul province. Personal Information Form, Scale of Attitude towards Scientific Research were used as data collection tool. According to the results; Preschool teacher candidates’ levels of reluctance to help researchers and negative attitudes towards research are lower when compared to Turkish language teacher candidates. Preschool teacher candidates’ positive attitudes towards researchs and researchers are higher when compared to Turkish language teacher candidates. Guidence and psychological counselor candidates’ negative attitudes towards research are lower when compared to Turkish language teacher candidates. The levels of reluctance to help researchers of male teacher candidates are higher when compared to female teacher candidates. Negative attitudes towards research of the teacher candidates who do not take the course of scientific research methods are higher when compared to the teacher candidates who take the research methods course. The teacher candidates’ attitudes towards research do not vary by age, grade level and the academic success average.
* Fatma Yaşar Ekici. İstanbul Sabahattin Zaim Üniversitesi, Eğitim Fakültesi, Okul Öncesi Öğretmenliği Ana Bilim Dalı, İstanbul, Türkiye.
Keywords: Preschool teacher candidate; Attitude towards scientific research